An Investigation of EFL Students’Perspectives on Using Digital Storytelling to Enhance Self-Directed Learning: A Case Study of EFL Thai Learners - Ponhan, Sutthinee - (มนุษยสังคมสาร (มสส.) คณะมนุษยศาสตร์และสังคมศาสตร์ มหาวิทยาลัยราชภัฏบุรีรัมย์, 2020)
This quasi-experimental study aimed at investigating the students’ perspectives on using digital storytelling for improving self-directed learning in EFL learners at Ubon Rachathani Rajabhat University. Data was collected via semi-structured interviews from nine students classified into three groups with different English ability levels; high, moderate and low, studying English for Communication and Work in the third semester of 2016, and was analysed through content analysis. The findings indicated that learning through digital storytelling could improve self-directed learning: self-planning, self-finding resource, self-control, and self-reflection. Thus, instructors should encourage this learning strategy during instruction and integrate the strategy in every field of education and life if they would like to increase their self-directed learning.